Wolfram Alpha (AI): Between Technological Transformation and Ethical Ideas in Education - Sampurno, Margo Teguh (Proceeding International Conference on Religion, Science and Education, 2024)
This article examines the development of the digital world with the presence of artificial intelligence such as Wolfram Alpha in fulfilling the accessibility of accurate and scientific information, as one of the important instruments in assisting human work. The logical consequence of modern civilisation makes "efficiency and effectiveness" an important milestone in a person’s mobility, including the need for information with technological bargaining power in the aspect of analysis in decision making. On the other side, the ease of access offered by artificial intelligence has been criticised, especially in the field of education. I argue that artificial intelligence contributes to the flexibility of the learning process between teachers and students, especially in understanding learning materials, but other trends can threaten the creativity and reasoning process in students. I pointed out that the role of teachers is slowly being replaced by the presence of artificial intelligence with its millions of information databases spread across the internet. Thus, building an educated generation that will coexists with technology in the future, must also include the moral dimension and mentality of an educated person.